STRUKTUR KOMUNITAS ZOOPLANKTON DI DANAU OPI JAKABARING PALEMBANG - Kusmeri, Lusi; Rosanti, Dewi (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2015)
ABSTRACTResearch on the structure of zooplankton community in Lake OPI Jakabaring Palembang was held in November 2014 until January 2015 in the Lake District of Seberang Ulu OPI 1 Palembang, aims to determine the community structure of zooplankton that are in there. Zooplankton samples were taken from three stations, are the left, center and right of the lake. Samples are identified, and analyzed are abundance, dominance, and diversity index. Physical and chemical parameters measured in field waters that include brightness, depth, temperature, DO and pH. Results showed that the composition of zooplankton consists of 10 species, were Cyclops sp, Brachionus falcatus, Keratella sp, Trichocerca longiseta, Nauplius sp, Philodina sp, Alona sp, Diaptomus sp, Leydigia sp and Bathynella morimolpi. Abundance highest total in the three stations owned by Cyclops sp species, totaling 10 ind/l. The highest dominance index has a value of 0.206, so it can be said there is no species that dominated the waters of the lake. Zooplankton diversity at all three stations categorized as low, with diversity index between 0.136 to 0.212. Keywords: community structure, zooplankton, lakes OPI